Biodiversity of Reef Fishes in Three Small Outer Islands of West Papua, Indonesia - Risandi Dwirama Putra; Petrus Christianus Makatipu; I Wayan Eka Dharmawan; Frensly Damianus Hukom; Muhammad Abrar; Rikoh Manogar Siringoringo; Ni Wayan Purnamsari; Aditya Hikmat Nugraha; Pradipta Agustina; Khairunnisa Khairunnisa; Asep Mulyono; MD Jayedul Islam (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Coral fish groups have a very strong dependence on coral reef ecosystems. Nusa Manggala Expedition was carried out for twenty days to explore basic data on the diversity of species of coral reef fish in the Liki, Bepondi, and Miossu Islands. Assessment of coral fish assemblages using Underwater Visual Census (UVC). Four hundred and thirty-two species of fifty families of reef fishes found during the 2nd session the Nusa Manggala expedition in Liki, Bepondi, and Miossu islands, northern Papua. Four species (Mobula tarapacana, M. alfredi, Oxymonacanthus longirostris, Bolbometopon muricatum, and Plectropomus areolatus) and one species (Cheilinus undulatus) categorized of IUCN as Vulnerable (VU) and Endangered (EN), respectively, were recorded in this study. There is unique pattern of reef fishes’ composition in small outer islands location in pristine location that shows Pomacentridae and Labridae were almost in the same number as Gobiidae, Apogonidae, Serranidae, Chaetodontidae, and Acanthuridae. In addition, the results showed that the Liki and Miossu islands and Bepondi Island included at the Coral Fish Diversity Index (CFDI) as an extraordinary and excellent category of marine fish, respectively. The results of the expedition showed that the Liki Islands and Miossu Island had an extraordinary category of marine fish, and Bepondi Island had an excellent category of sea fish. The culture of local people in Papua called "Sasi" prove to provide full protection to the ecosystem and have a positive impact on high diversity of reef fishes.